Cafe-au-lait spots as a clinical sign of syndromes (Research, Society and Development, 2021)
Several studies describe the frequent association of cafe-au-lait spots with neurofibromatosis. However, many other genetic diseases might be associated with the presence of café-au-lait spots. Several genetic diseases are rare. In most cases, syndromes present themselves as a set of signs and symptoms that may present varied penetrance, therefore largely reducing the percentage of final diagnosis. Exploration of clinical symptomatology is essential for the understanding and diagnosis of syndromes. In this review, we conduct an extensive literature search looking for research that investigated diseases that may be present simultaneously with the cafe-au-lait spots. A total of 60 genetic diseases were found, all of them rare. These syndromes were evaluated based on their most relevant features and described in a summary of the typical, general, and head and neck findings. The available OMIM number, mode of inheritance, chromosome, mutated genes, and affected proteins were also listed. The considerable variety of diseases associated with the presence of cafe-au-lait spots and the fact that many of these conditions affect various organ systems with diverse phenotypic presentations is a diagnostic and therapeutic challenge. The objective of this study was to provide health professionals with an instrument containing a broad spectrum of genetic diseases coincident with the presence of cafe-au-lait spots in order to facilitate the differential and final diagnosis of these syndromes.